2012
DOI: 10.3389/fpsyg.2012.00451
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic Cues to Word Order: What Level of Representation?

Abstract: Within language, systematic correlations exist between syntactic structure and prosody. Prosodic prominence, for instance, falls on the complement and not the head of syntactic phrases, and its realization depends on the phrasal position of the prominent element. Thus, in Japanese, a functor-final language, prominence is phrase-initial, and realized as increased pitch (^ Tōkyō ni “Tokyo to”), whereas in French, English, or Italian, functor-initial languages, it manifests itself as phrase-final lengthening (to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 35 publications
1
54
1
Order By: Relevance
“…The familiar VO prosody condition was not tested. Recent work with monolingual French infants 19 , a language with word order and phrasal prosody similar to English 14 , has already revealed that monolingual infants can use trochaic prosody to guide word order preferences. Also, a VO condition would not allow us to tease apart the effects of familiarity and a universal iambic-trochaic bias.…”
Section: Resultsmentioning
confidence: 99%
“…The familiar VO prosody condition was not tested. Recent work with monolingual French infants 19 , a language with word order and phrasal prosody similar to English 14 , has already revealed that monolingual infants can use trochaic prosody to guide word order preferences. Also, a VO condition would not allow us to tease apart the effects of familiarity and a universal iambic-trochaic bias.…”
Section: Resultsmentioning
confidence: 99%
“…The data of another 12 infants were excluded due to looking time too short (1), fussiness (9), and ceiling looking (2).…”
Section: Methodsmentioning
confidence: 99%
“…8 Furthermore, infants' prosody-based phrasal grouping is in line with the head direction of their native language. For example, French-learning 8-month-olds prefer groupings with weakinitial and strong-final syllables, 9 the typical prosody found in a head-initial language.…”
Section: Introductionmentioning
confidence: 99%
“…Let us focus on the two main ideas that we have seen so far, which are that (i) according to the "globularization hypothesis" of Boeckx and Benítez-Burraco (2014a,b), the postnatal globularization of the brain is an essential ingredient for the development of our syntactic capacities, and that (ii) according to the "prosodic bootstrapping hypothesis" of Mehler et al (1988), Christophe et al (2003), Bernard and Gervain (2012), Gervain and Werker (2013), Langus and Nespor (2013) and others, children use prosody in order to infer the syntactic pattern of the language they are acquiring.…”
Section: Synthesis: the "Globularization Hypothesis" As A Developmentmentioning
confidence: 99%
“…i.a. Mehler et al, 1988;Christophe et al, 2003;Bernard and Gervain, 2012;Gervain and Werker, 2013;Langus and Nespor, 2013) 6 . In particular, a number of authors have proposed that the relative order between heads and their complements strongly correlates with the rhythmic type of the language.…”
Section: The "Prosodic Bootstrapping" Hypothesismentioning
confidence: 99%